Construction Policy for Person with Disabilities Based on Value of Pancasila Justice - Sutrisno, Endang; Permana, Ipik; Akbar, Gilar (International Journal of Psychosocial Rehabilitation, 2020)
Persons with disabilities must be treated equally and the same as most other citizens in general, the responsibility of the State must fulfill its obligations without exception. Legal norms have explicitly mandated fair treatment. Legislation products that are formulated must still be based on Pancasila as a boundary line for good behavior parameters, as well as the philosophical Nation’s view of life. The study of policies for persons with disabilities towards public services that have been provided by the State must rely on justice with Pancasila values, this is important because the guidelines for formulating the order are reflected in the Precepts of Pancasila. The approach in this study is juridical-normative, focuses on legal products that favor to the interests of society as a whole without exception, considering that public service is a basic right of citizens and the responsibility of the Government to fulfill equality of human rights including in the form of public service facilities that can be accessed by persons with disabilities.